PENGARUH PERSEPSI KEPERCAYAAN, PERSEPSI RISIKO, DAN MANFAAT TERHADAP MINAT PENGGUNAAN MOBILE BANKING BANK SYARIAH - Moh. Abd. Rahman; Nurul Fadila; Nuntupa Nuntupa (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2023)
Banking is one of the advanced information technologies that can be used to achieve high levels of customer service and new technologies that allow banking transactions via mobile phones. For bank customers, this application will support their transaction banking if they find it useful and easy to use. This study aims to examine the factors that influence the intention to use internet banking services. This research was conducted at the Sharia Banking Faculty of Islamic Economics and Business, Zainul Hasan Genggong Islamic University. Researchers received responses from 97 respondents who were students of Islamic banking study programs who had used internet banking. Data were analyzed using the method of literature study, with qualitative methods with analytical models and direct interviews to obtain information. The results of this model analysis show that the constructs of perceived benefits, perceived risks, and trust affect the intention to use internet banking. Although the perceived ease of use does not affect the intention to use the Internet Bank. This means that the intention to use internet banking is influenced by the construct of perceived benefits, perceived ease of use, and trust.